Fenomena Etos Kerja dalam Perspektif Islam - Misbahus Surur (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
The work ethic is a reflection of a view of life that is oriented towards divine values. In addition, work ethic is related to achieving material success. To achieve a good work ethic, there is a background that underlies the desire to achieve it optimally, namely because of the desire to get a reward for seeking Allah's pleasure so that it will be of worship and worldly value and some are want to get material material rewards in the form of money or salary, in order to meet the needs of his family. However, it should be noted that the goal is material means remuneration of wages, salaries are commensurate, sometimes misinterpreted by getting as much reward as possible which in the end is only used for fun. Islam views the achievement of the work ethic in a balanced way. Islam emphasizes the principle of balance, insight into harmony and harmony between the worldly and the hereafter, between material and spiritual, between physical and spiritual, between work to meet family needs and worship. This means that in addition to success in achieving the life of the world, but the hereafter is also not neglected.